Promoting English language learning among limited English proficiency learners through movies - Rozmel Abdul Latiff; Nor Hasni Mokhtar; Raja Hanani Raja Mushahar; Michi Farida Abdul Halim (Penerbit Universiti Kebangsaan Malaysia, 2021)
English language learning in a non-native environment is always a challenge. This is especially so among limited English proficiency (LEP) learners. Despite having eleven years of instructions in English in primary and secondary school, there are still quite a number of LEP learners entering the university. This may be attributed to lack of exposure to the language, as classroom instruction alone is not sufficient for mastery of a second language. Although English is widely spoken in Malaysia, this does not apply to all communities, especially in rural areas. In such circumstances, watching movies in the target language can provide the necessary exposure, the ample amount of listening and reading in the target language, which provides the comprehensible input essential for language acquisition. Movies also come with closed captions, which not only help the learner recognize the words but also enable them to look up the words in a dictionary. An action research was conducted to investigate the effectiveness of using movies in a Foundation English course. This paper details the implementation of movie viewing in the course and presents the usability and appropriateness of using English movies in the acquisition of English language skills and creating cultural awareness among LEP learners. Finally, this paper highlights the learners’ responses regarding their experience in watching the movies. These responses provide invaluable insights into the impetus for future use of movies in the ESL classroom.